Partisipasi Masyarakat Dalam Pengelolaan Desa Wisata Koja Doi Di Kecamatan Alok Timur Kabupaten Sikka - Laga Hae, Asri Kristiansi; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 9 No 1 (2021): VOL 9, NO 1 (2021): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATA, 2021)
This study discusses that community participation in the management of Koja Doi Rural Tourism is very important for the development of Koja Doi Village. This research is intended to identify management identification and community participation in the management of Koja Doi Rural Tourism in Alok Timur District, Sikka Regency. The research used qualitative methods with qualitative and quantitative types of data. Data sources are primary data and secondary data. Data collection was carried out by interview, library research and arrangement methods. The technique to determine the informants used were purposive sampling. The data analysis technique used in this research is descriptive qualitative analysis. The results of this study indicate that the management of Koja Doi Rural Tourism is carried out by Village-Owned Enterprises (BUMDes) Monianse and Kelompok Sadar Wisata (Pokdarwis) Monianse. At first the type of community participation in Koja Doi is a form of Induced Participation which means that the community participation in Koja Doi Village were being encouraged by the stakeholders, but in 2016 after forming BUMDes and Pokdarwis Monianse, the existing form of participation became spontaneous, this could be seen from locals participation after the locals starts to spontaneously managing and taking care of their village tourism. Keyword: Community Participation, Management, Rural Tourism, Koja Doi